Fructo-Oligosaccharide (DFA III) Feed Supplementation for Mitigation of Mycotoxin Exposure in Cattle—Clinical Evaluation by a Urinary Zearalenone Monitoring System - Toda, Katsuki (Toxins (Basel), 2018)
The potential effect of difructose anhydride III (DFA III) supplementation in cattle feed was evaluated using a previously developed urinary-zearalenone (ZEN) monitoring system. Japanese Black cattle from two beef herds aged 9–10 months were used. DFA III was supplemented for two weeks. ZEN concentrations in feed were similar in both herds (0.27 and 0.22 mg/kg in roughage and concentrates, respectively), and below the maximum allowance in Japan. ZEN, α-zearalenol (α-ZOL), and β-ZOL concentrations in urine were measured using LC/MS/MS the day before DFA III administration, 9 and 14 days thereafter, and 9 days after supplementation ceased. Significant differences in ZEN, α-ZOL, β-ZOL, and total ZEN were recorded on different sampling dates. The concentration of inorganic phosphate in DFA III-supplemented animals was significantly higher than in controls on day 23 (8.4 vs. 7.7 mg/dL), suggesting a possible role of DFA III in tight junction of intestinal epithelial cells. This is the first evidence that DFA III reduces mycotoxin levels reaching the systemic circulation and excreted in urine. This preventive effect may involve an improved tight-junction-dependent intestinal barrier function. Additionally, our practical approach confirmed that monitoring of urinary mycotoxin is useful for evaluating the effects of dietary supplements to prevent mycotoxin adsorption.